Optical dating of Holocene paleosol development and climate changes in the Yili Basin, arid central Asia. (June 2019) - Wang, Leibin; Jia, Jia; Zhao, Hui; Liu, Hao; Duan, Yanwu; Xie, Haichao; Zhang, David D; Chen, Fahu
Optically stimulated luminescence (OSL) dating was conducted on the K-feldspar and quartz fractions of a Holocene loess-paleosol sequence in the Yili Basin, in the core area of arid central Asia (ACA). Age overestimation using the post-IR IR (pIR50 IR170 ) signals from feldspar was observed for paleosols, because of poor bleaching prior to deposition. Therefore, a reliable age framework for the studied section was established using OSL dating of coarse-grained quartz, combined with a Bacon age model. A total of 18 OSL ages were obtained from a 2.5-m-loess/paleosol sequence with age range of 17.4–0.4 ka. Magnetic and grain-size proxies were used to reconstruct environmental changes during the studied interval, and the results indicate that paleosol development commenced at ~6 ka in the Yili Basin, which is consistent with previous studies in the Xinjiang region. Dust accumulation rates (DARs) and end-member analysis (EMA) of the grain-size frequency distributions were used to infer variations in the Westerlies during the Holocene, and the results suggest that the Westerlies were the main source of excess moisture in ACA during the studied interval.